NEUTRAL CURRENTS AND GLASHOW-ILIOPOULOS-MAIANI MECHANISM IN SU(3)L-CIRCLE-TIMES-U(1)N MODELS FOR ELECTROWEAK INTERACTIONS - Montero, J. C.; Pisano, F.; PLEITEZ, V (American Physical Soc, 1993)
We study the Glashow-Iliopoulos-Maiani mechanism for flavor-changing neutral-current suppression in both the gauge and Higgs sectors, for models with SU(3)L X U(1)N gauge symmetry. The models differ from one another only with respect to the representation content. The main features of these models are that in order to cancel the triangle anomalies the number of families must be divisible by three (the number of colors) and that the lepton number is violated by some lepton-gauge bosons and lepton-scalar interactions.